137 Impact of absolute lymphocyte count (ALC) frequency on detection of dimethyl fumarate–associated lymphopenia. Issue 9 (12th August 2022) - Brownlee, Wallace; Hadipour-Rahimabadi, Shooka; Davies, Heather; Belviso, Nick; Shen, Changyu; Kapadia, Shivani; Levin, Seth; Li, Hanyue
Abstract : Introduction: Lymphopenia is a known adverse event of dimethyl fumarate (DMF) with treatment dis- continuation recommended for patients with severe prolonged (≥6 months) lymphopenia. Because of the COVID-19 pandemic burden on healthcare systems, we retrospectively examined the impact of absolute lymphocyte count (ALC) monitoring frequency (every-3-months vs every-6-months) on lym- phopenia detection. Methods: Samples from patients enrolled in phase 3 trials (DEFINE/CONFIRM) and the extension study (ENDORSE) were retrospectively analysed using 3-month or 6-month intervals. Lymphopenia was defined as ALC <0.91x109/L and severe lymphopenia as ALC <0.5×109/L. Times to the first lymphopenia event and first severe lymphopenia event were estimated using Kaplan-Meier methods. Results: The analysis included 741 patients. There were 355 lymphopenia cases (76 severe) with 3-month monitoring, and 314 cases (70 severe) with 6-month monitoring. Over 120 months, incidence of first lympho- penia event was significantly different for 3-month vs 6-month monitoring (difference range: 2.64%–6.54%; P=0.0088). Incidence of first severe lymphopenia event was not significantly different for the two intervals (P=0.5866). Proportions of patients with severe prolonged lymphopenia with 3-month and 6-month moni- toring were similar (4.0% vs 4.2%). Conclusions: The results of this study may be informative to clinicians managing pandemic-related health- care resource burdens. Support: Biogen. Disclosures on poster.